Earnings-based compensation schemes and fringe benefits practices : an analysis in the Singapore context - Koh, Yit Yin (2014)
The proliferation of fringe benefits and growing popularity of earnings-based compensation schemes in Singapore Companies have motivated the project group to look more in depth into this area of study. It is therefore, the aim of this study to provide an insight into the provisions of fringe benefits and earnings-based compensation schemes, namely Share Option Scheme, Profit Sharing and Variable Pay/Bonus. The study also highlights the sufficiency of using profitability as a financial performance measure to determine the availability of the earnings-based compensation schemes.